Momentos fracionários e localização dinâmica para o modelo de Anderson discreto multidimensional - Sousa, José Vanterler da Costa [UNESP] (2014)
In this work we present a study on the phenomenon of dynamic localization for multidimensional discrete Anderson model, through the method of fractional moments of the Green’s function in infinite and finite volumes. We discuss spectral and dynamic properties of localization of the model and we present the proof that for sufficiently large disorder, the Anderson model is dynamically located in its spectrum. As a consequence, we obtain that this model has pure point spectrum a.e. with exponentially decaying eigenfunctions.